Unusual foreign body insertion in rectum and vagina in schizophrenic patient - Mushtaq, Raheel; Shoib, Sheikh; Bhat, Mudasir Hamid; Shah, Tabindah; Mushtaq, Sahil; Hussain, Tajamul; Shah, Raheeb (International Journal of Research in Medical Sciences, 2017)
Insertion of foreign body in to the body is rare in medical literature. Here we report a case of 21 year old female who presented to emergency with acute abdomen and on detailed evaluation turned out to be schizophrenia. Our patient had history of insertion of ball pen in rectum following command hallucination. The foreign body was later removed through laparotomy. The cause of insertion of foreign body are multiple from command hallucination, suicidal attempt, erotism to somatic delusions. Thus the clinician should always be vigilant while dealing with psychiatric patients as sometimes impacted foreign body can present as acute emergency.